Inkulkasi Nilai Karakter dalam Teks Cerita Fantasi pada Peserta Didik - Sahman, Sahman; Haritani, Hartini; Murcahyanto, Hary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the character values expressed by students in fantasy stories, describe how students express character values in fantasy stories, and describe what character values are dominant in fantasy stories. The method used in this study is a descriptive qualitative method using a case study approach. Sources of data in this research are 30 fantasy stories of students taken according to the criteria of fantasy stories. This research was conducted at SMP Negeri 3 Keruak. Data collection techniques used are questionnaires and documentation. The result of this research is that fantasy story media is one way for teachers to implement character values and identify those character values. After being identified, there are various character values found in students' fantasy stories, namely religious character values, honesty, tolerance, discipline, hard work, independent, creative, democratic, curiosity, love for the homeland, friendly/communicative, peace-loving, fond of reading. , social care, and responsibility. The most dominant or most dominant character value of all students' fantasy stories is the curiosity character value as many as 18 findings. The conclusion of this research is that in the fantasy story text of students there is a content of character values.